IMMU-11. SELECTIVE ENRICHMENT OF SUPPRESSED IMMUNE CELLS IN THE TUMOR MICROENVIRONMENT CORRELATES WITH ESTABLISHMENT OF DISTINCT IMMUNOLOGIC NICHES IN HUMAN GLIOBLASTOMAS CONTACTING THE LATERAL VENTRICLE. (12th November 2021) - Bartkowiak, Todd; Brockman, Asa; Mobley, Bret; Mistry, Akshitkumar; Barone, Sierra; Hayes, Madeline; Roe, Caroline; Sinnaeve, Justine; Leelatian, Nalin; Greenplate, Allison; Chambless, Lola; Thompson, Reid; et al.
Abstract: Glioblastomas (GBM) account for 60% of adult primary brain tumors. With few advances in therapeutics, median overall survival remains 15-months post-diagnosis. Immunotherapies may provide therapeutic benefit in GBM patients; however, no predictive immune features currently inform therapeutic stratification in GBM. We have shown that, independently of known prognosticators, radiographic tumor contact with the lateral ventricle (C-GBM) correlates with 7-months worse prognosis compared to patients with ventricle non-contacting GBM (NC-GBM). This study sought to characterize the GBM immune microenvironment and identify targetable mechanisms of immunosuppression correlating with worse outcomes in C-GBM. Primary glioblastoma specimens were resected in accordance with the Declaration of Helsinki (IRB #131870). Twelve patients presented with C-GBM and thirteen with NC-GBM. Machine learning tools applied to mass cytometry data characterized tumor-infiltrating immune populations and identified biomarkers correlating with C-GBM and patient survival. C-GBM tumors were enriched in blood-derived macrophages compared to NC-GBM (19 ± 8% vs. 6 ± 2%; p< 0.001) and depleted in lymphocytes (2.9 ± 1% vs. 7.6 ± 2%; p< 0.001) and tissue-resident microglia (1.8 ± 0.3% vs. 7 ± 3%; p< 0.001). Further, T cells in C-GBM co-expressed the checkpoint receptors PD-1 and TIGIT, suggesting acute T cell exhaustion. Multiplex immunohistochemistry (mxIHC) on matched FFPE tissue provided spatial context to risk-stratifying immune populations, and defined structured immunological niches within the TME. Macrophage-tumor niches were most common (36%), followed by T cell-microglia-tumor niches (26%). Within niches, T cell-T cell interactions were more prevalent (log odds ratio = 0.90) whereas T cell-macrophage interactions were less prevalent (log odds ratio = -1.61). These findings suggest that factors within the periventricular space may influence antitumor immunity within tumors, and identify clinically targetable immune biomarkers in glioblastoma. Notably, radiologic assessment of lateral ventricle contact by standard-of-care MRI may guide clinical trial design for immunotherapies in neuro-oncology.